Estrategias para aumentar la competitividad en los centros de acopio de reciclaje pet en la ciudad de Bogotá periodo 2005-2017 (2018)
In the following project, a detailed description of the PET plastic recycling industry is carried out from 2005 to 2017, specifically in companies linked to the sector in Bogotá DC, all with the need to increase their competitiveness in the PET waste market, raw material, commercialization and transportation to the integral recycling plants.